Conserved TRAM Domain Functions as an Archaeal Cold Shock Protein via RNA Chaperone Activity - Zhang, Bo; Yue, Lei; Zhou, Liguang; Qi, Lei; Li, Jie; Dong, Xiuzhu (Frontiers in Microbiology, 2017)
Cold shock proteins (Csps) enable organisms to acclimate to and survive in cold environments and the bacterial CspA family exerts the cold protection via its RNA chaperone activity. However, most Archaea do not contain orthologs to the bacterial csp. TRAM, a conserved domain among RNA modification proteins ubiquitously distributed in organisms, occurs as an individual protein in most archaeal phyla and has a structural similarity to Csp proteins, yet its biological functions remain unknown. Through physiological and biochemical studies on four TRAM proteins from a cold adaptive archaeon Methanolobus psychrophilus R15, this work demonstrated that TRAM is an archaeal cold shock protein and exhibits RNA chaperone activity. Three TRAM encoding genes (Mpsy_0643, Mpsy_3043, and Mpsy_3066) exhibited remarkable cold-shock induced transcription and were preferentially translated at lower temperature (18°C), while the fourth (Mspy_2002) was constitutively expressed. They were all able to complement the cspABGE mutant of E. coli BX04 that does not grow in cold temperatures and showed transcriptional antitermination. TRAM3066 (gene product of Mpsy_3066) and TRAM2002 (gene product of Mpsy_2002) displayed sequence-non-specific RNA but not DNA binding activity, and TRAM3066 assisted RNases in degradation of structured RNA, thus validating the RNA chaperone activity of TRAMs. Given the chaperone activity, TRAM is predicted to function beyond a cold shock protein.